Morphological and immunohistochemical (Troponin C) evaluation of cardiac lesions in dogs with chronic kidney disease - D’Avila, Mariana Sequeira (2016)
ABSTRACT. D’Avila M.S., França T.N., Peixoto P.V., Peixoto T.C., Santos A. M., Costa S.Z.R., Santos R.S., Gonçalves T. & Nogueira V.A. [Morphological and immunohistochemical (Troponin C) evaluation of cardiac lesions in dogs with chronic kidney disease.] Avaliações morfológica e imuno-histoquímica (Troponina C) de lesões cardíacas em cães com doença renal crônica. Revista Brasileira de Medicina Veterinária, 38(Supl.2):128-138, 2016. Programa de Pós-Graduação em Medicina Veterinária, Área de Concentração em Patologia Animal, Universidade Federal do Rio de Janeiro, Rodovia BR-465 Km 7, Seropédica, RJ 23890-000, Brasil. E-mail: mariana_davila@hotmail.com This study had the objective (1) to verify the correlation between chronic kidney disease (CKD) and heart failure as well to evaluate the real extent of these changes and (2) to determine the reliability of the immunohistochemistry test using the human anti-troponin C antibody in detection of heart failure in dogs. Fragments of heart and kidneys paraffin embedded of 22 dogs (11 males and 11 females) with previous diagnosis of chronic kidney disease were used. The animals were from Department of Veterinary Pathology of the Federal Rural University of Rio de Janeiro (UFRRJ) and Federal University of Bahia (UFBA), from different breeds and they had between 11 months and 18 years old. The macroscopic examination revealed, in the heart of five dogs, moderate to accentuated thickening of left ventricular wall. It was also found endocardiosis in different degrees. Extrarenal uremic lesions included ulcerative glossitis and stomatitis, pneumopathies and uremic gastropathy, stomach mucosal ulceration and mineralization in the pharynx, larynx and subpleural up to intercostal muscles. Chronic renal lesions were characterized by marked decrease in volume, firm texture, irregular surface and changes in cortico-medullary relationship. Microscopic evaluation revealed, in the kidneys of all dogs, different degrees of lesion. In severe cases, there was hyalinization and glomerular sclerosis, linfoplasmocitic inflammation, coagulative necrosis of the tubular kidney epithelial cells, interstitial fibrosis and mineralization. In the heart of 16 animals, it was observed groups of hypereosinophilic myocytes with homogeneous aspect, and in some cases, there was striation loss and pyknosis; in 14 dogs had swelling, linfoplasmocitic inflammation and mineralization. In other 2 animals swollen and vacuolization of cardiac cells were observed and, in 3, marked coagulative necrosis. In 11 dogs it was observed, in heart vessels, mild cell swelling of endothelial cell to necrosis, with deposition of eosinophilic material in the vascular wall and mineralization. Immunohistochemistry evaluation revealed, in all dogs, several groups of myocytes with significant reduction or absence of immunoreactivity for anti-troponin C antibody. This decrease in imunoreactivity occurred usually on the same myocytes with specific changes in HE stain, ranging from swelling, cytoplasmatic hypereosinophilic, striation loss, cell lysis, karyolysis and inflammatory infiltrate predominantly composed of lymphocytes and plasma cells. It is suggested that myocardial lesions observed in this study are closely correlated to vascular changes, resulting from long duration uremia and/or combination of metabolic and cellular changes which occurs in cardiorenal syndrome type IV, in which chronic involvement kidney may to induce chronic injuries in the heart.